SARI suppresses colitis‐associated cancer development by maintaining MCP‐1‐mediated tumour‐associated macrophage recruitment - Dai, Lei (J Cell Mol Med, 2019)
SARI (suppressor of AP‐1, regulated by IFN) impaired tumour growth by promoting apoptosis and inhibiting cell proliferation and tumour angiogenesis in various cancers. However, the role of SARI in regulating tumour‐associated inflammation microenvironment is still elusive. In our study, the colitis‐dependent and ‐independent primary model were established in SARI deficiency mice and immuno‐reconstructive mice to investigate the functional role of SARI in regulating tumour‐associated inflammation microenvironment and primary colon cancer formation. The results have shown that SARI deficiency promotes colitis‐associated cancer (CAC) development only in the presence of colon inflammation. SARI inhibited tumour‐associated macrophages (TAM) infiltration in colon tissues, and SARI deficiency in bone marrow cells has no observed role in the promotion of intestinal tumorigenesis. Mechanism investigations indicated that SARI down‐regulates p‐STAT1 and STAT1 expression in colon cancer cells, following inhibition of MCP‐1/CCR2 axis activation during CAC development. Inverse correlations between SARI expression and macrophage infiltration, MCP‐1 expression and p‐STAT1 expression were also demonstrated in colon malignant tissues. Collectively, our results prove the inhibition role of SARI in colon cancer formation through regulating TAM infiltration.